THE ROLE OF THE EUROPEAN UNION AS AN INTERNATIONAL ACTOR IN DEVELOPING COUNTRIES - Bharti, Mukesh Shankar; Bharti, Sushant Shankar (Torun International Studies, 2024)
This research aims to discuss the role of the European Union (EU) in developing countries in establishing democracy, rule of law and development. The EU has been considered an international actor since its establishment. Various literatures argue that the EU plays a significant role in developing countries. In this context, this study highlights the various roles of the EU and their multi-dimensional engagement in developing countries. Furthermore, the article also traces the EU’s actorness through its cooperation in several areas of engagement such as international cooperation in global peace and conflict settlement, military, sustainable development, economic cooperation, humanitarian background, cultural engagement and other activities. The qualitative study is applied here to generate an argument through the primary and secondary sources of data, where the research traces vis-à-vis the review of books and articles of the scholars in international relations. The empirical analysis aims to highlight the main problems of developing countries and evaluate the role of the EU as a problem-solving actor for better social development. As a result, the EU itself and its various associate institutions have been working in Asia, Africa, Latin America and Oceanian countries in many sectors for a stable government with democratic norms and ethos. The initial findings of this article are that the EU is the largest aid provider in many countries of Asia and Africa and supports institutional development in war zone regions in the world.